2023
DOI: 10.1080/20002297.2023.2213111
|View full text |Cite
|
Sign up to set email alerts
|

Newly identified pathogens in periodontitis: evidence from an association and an elimination study

Abstract: We assessed the level of evidence for the presence of new periodontal pathogens by (i) comparing the occurrence of non-classical periodontal taxa between healthy vs. periodontitis patients (Association study); (ii) assessing the modifications in the prevalence and levels of these species after treatments (Elimination study). In the Association study, we compared the prevalence and levels of 39 novel bacterial species between periodontally healthy and periodontitis patients. In the Elimination study, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…An association between Haemophilus and endometriosis was observed, along with its potential relationship with estrogen levels and hormonal treatment [66,67]. On the other hand, Haemophilus influenzae has been associated with the etiology of periodontitis [68], a condition frequently found in patients with endometriosis. The finding suggests that endometriosis might have environmental conditions corresponding to outer and inner FRT sites that limit colonization for some microbial genera.…”
Section: Discussionmentioning
confidence: 99%
“…An association between Haemophilus and endometriosis was observed, along with its potential relationship with estrogen levels and hormonal treatment [66,67]. On the other hand, Haemophilus influenzae has been associated with the etiology of periodontitis [68], a condition frequently found in patients with endometriosis. The finding suggests that endometriosis might have environmental conditions corresponding to outer and inner FRT sites that limit colonization for some microbial genera.…”
Section: Discussionmentioning
confidence: 99%
“…Socransky et al elucidated that the bacteria in dental plaque form different complexes, of which the red complex bacteria consisting of Porphyromonas gingivalis (P. gingivalis), Treponema denticola (T. denticola), and Tannerella forsythia (T. forsythia) along with the orange complex bacteria are considered to be the most putative periodontal pathogens [7]. Currently, open-ended microbial identification techniques and next-generation sequencing techniques have greatly increased the understanding of microbial diversity and newer species existing in dental plaque [8,9]. This knowledge has helped us to understand the microorganisms that are involved in the dysbiosis that occurs as part of periodontal disease.…”
Section: Introductionmentioning
confidence: 99%
“…Paster et al, in 2001, pointed out the presence of novel species that could play a part in dysbiosis and periodontitis [10]. Recent studies and systematic reviews have found further proof of these new species and their putative role in periodontal pathogenesis [8,9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Based on the current model from the oral microbiome project, it is one of the marker organisms that is now identified to be significant to the pathogenic structure of biofilms associated with periodontal inflammation and is considered an important organism for periodontal disease (Dahlen & Leonhardt, 2006;Kumar et al, 2005Kumar et al, , 2006Schlafer et al, 2010). The presence of F. alocis is now observed at significantly higher levels in periodontal disease sites compared to healthy sites (Antezack et al, 2023;Araújo et al, 2023;Dahlen & Leonhardt, 2006;Griffen et al, 2012;Kumar et al, 2005;Lafaurie et al, 2023;Lee et al, 2020;Nemoto et al, 2021;Schlafer et al, 2010;Veras et al, 2023). A recent study by Wirth et al (2021) placed F. alocis in the group of 'red complex bacteria' , where F. alocis was 1 of the 10 most abundant bacteria in the diseased periodontal pocket community.…”
Section: Introductionmentioning
confidence: 99%